The influence of social media on learners' mental health - Tiara Safina; Fatima Meilani Putri Redyno; Rizqina Rahmatika; Berliana Julianti; Nur Kholipah (HAFECS PRESS, 2025)
Today, the phenomenon of massive social media use raises concerns about the mental and emotional health of individuals, especially among adolescents and young adults. This phenomenon even affects students' interest in learning. The solution to this problem is health education, which aims to raise awareness of the negative impacts of social media use and encourage wise use. In this study, the integration of health education about social media in the school curriculum can help better understand how to use social media healthily and wisely. Therefore, it is important to pay attention to the problem of addiction due to social media use in adolescents to protect mental health. The purpose of this study is to see how far the effect is, and how risk prevention to deal with this to adolescents or students. Based on the results of the study, according to the results of the coefficient of determination, it can be concluded that Instagram social media can affect the mental health of students by 58.5%. This finding highlights the need for health education interventions in the school environment to minimize the risk of mental health disorders caused by excessive use of social media. Abstrak. Dewasa ini, fenomena penggunaan media sosial yang masif menimbulkan kekhawatiran terhadap kesehatan mental dan emosional individu khususnya kalangan remaja dan dewasa muda. Fenomena ini bahkan memengaruhi minat belajar peserta didik. Solusi masalah ini adalah pendidikan kesehatan yang dimana bertujuan untuk meningkatkan kesadaran akan dampak negatif penggunaan media sosial dan mendorong penggunaan yang bijak. Dalam penelitian ini, Adanya integrasi pendidikan kesehatan tentang media sosial dalam kurikulum sekolah dapat membantu memahami lebih baik cara menggunakan media sosial secara sehat dan bijak. Oleh karena itu, penting untuk memperhatikan masalah kecanduan akibat penggunaan media sosial pada remaja guna melindungi kesehatan mental. Tujuan penelitian ini untuk melihat pengaruhnya seberapa jauh, dan bagaimana pencegahan risiko untuk menangani ini kepada remaja atau siswa.Berdasarkan hasil penelitian, sesuai dengan hasil koefisien determinasi dapat disimpulkan bahwa media sosial Instagram dapat mempengaruhi kesehatan mental peserta didik sebesar 58,5%. Temuan ini menegaskan perlunya intervensi pendidikan kesehatan di lingkungan sekolah untuk meminimalkan risiko gangguan mental akibat penggunaan media sosial yang berlebihan.